Geochemical controls of iron on blue carbon stabilization in mangrove soils across micro- and macro-scales - Costa, Rodolfo Fagundes (2025)
Mangrove forests are globally recognized as highly efficient Blue Carbon ecosystems, yet the mechanisms controlling soil organic carbon (SOC) accumulation and stabilization remain poorly understood. This thesis investigates the geochemical role of iron (Fe) in regulating carbon dynamics in Brazilian mangrove soils across multiple spatial scales, combining national assessments, site-level surveys, and micro-scale analyses. Chapter 1 provides the first nationwide quantification of mangrove cover change in Brazil and its consequences for total ecosystem carbon stocks (TECS), establishing a baseline for carbon loss and emissions. Chapter 2 examines Fe-mediated preservation of SOC in Amazonian mangroves using sequential extractions, highlighting the role of reactive Fe phases as rusty sinks of organic matter. Chapter 3 explores how salinity gradients modulate Fe speciation and redox conditions, revealing competing stabilization pathways driven by oxides and sulfides. Chapter 4 evaluates the influence of contrasting geological settings on Fe transformations and carbon sequestration in Espírito Santo mangroves, demonstrating the pivotal role of pyritization and lithological inheritance. Finally, Chapter 5 integrates these findings to show geology as a primary driver of organomineral associations and Blue Carbon permanence, providing new parameters to improve predictive models of carbon stocks at regional to national scales. Collectively, the results demonstrate that FeOM interactions mediated by salinity and lithologyare key controls on the persistence of mangrove SOC. This work advances the mechanistic understanding of Blue Carbon stabilization and offers a scientific foundation for incorporating mangroves into conservation, restoration, and carbon market strategies in Brazil and other countries.